2004
DOI: 10.1021/ic034848a
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent Heterotrinuclear Complexes with Pt(diimine)(dithiolate) and Metal Diphosphine as Components

Abstract: Reactions of Pt(diimine)(tdt) (tdt =3,4-toluenedithiolate) with [M(2)(dppm)(2)(MeCN)(2)](2+) (M = Cu(I) or Ag(I), dppm = bis(diphenylphosphino)methane) gave heterotrinuclear complexes [PtCu(2)(tdt)(mu-SH)(dppm)(3)](ClO(4)) (1) and [PtCu(2)(diimine)(2)(tdt)(dppm)(2)](ClO(4))(2) (diimine = 2,2'-bpyridine (bpy) 2; 4,4'-dimethyl-2,2'-bipyridine (dmbpy) 3; phenanthroline (phen) 4, 5-bromophenanthroline (Brphen) 5) for M = Cu(I), but [PtAg(2)(tdt)(mu-SH)(dppm)(3)](SbF(6)) (6) and [PtAg(2)(diimine)(tdt)(dppm)(2)](SbF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(28 citation statements)
references
References 71 publications
1
27
0
Order By: Relevance
“…In the 31 P NMR spectra of Pt II −M I heteronuclear compounds 1 − 13 , typical P satellite peaks arising from the Pt−P coupling occur at 8.3−13.6 ppm with the J Pt - P value in the range of 1220−1300 Hz. 10a, In some cases, the Pt−P satellite signals show a moderate splitting that originates from the P−P couplings through P −CH 2 − P or/and P −Pt− P pathways with 2 J P - P = 30−35 Hz. For Pt II −Ag I heteronuclear compounds 1 − 5 and 13 , the P donors bound to the Ag I centers afford doublets or doublet of doublets centered at 1.6−2.7 ppm because of the effects of both Ag−P and P−P couplings with 1 J Ag - P = 515−530 Hz and 2 J P - P = 30−35 Hz.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the 31 P NMR spectra of Pt II −M I heteronuclear compounds 1 − 13 , typical P satellite peaks arising from the Pt−P coupling occur at 8.3−13.6 ppm with the J Pt - P value in the range of 1220−1300 Hz. 10a, In some cases, the Pt−P satellite signals show a moderate splitting that originates from the P−P couplings through P −CH 2 − P or/and P −Pt− P pathways with 2 J P - P = 30−35 Hz. For Pt II −Ag I heteronuclear compounds 1 − 5 and 13 , the P donors bound to the Ag I centers afford doublets or doublet of doublets centered at 1.6−2.7 ppm because of the effects of both Ag−P and P−P couplings with 1 J Ag - P = 515−530 Hz and 2 J P - P = 30−35 Hz.…”
Section: Resultsmentioning
confidence: 99%
“…Considerable attention has been paid to the chemistry of Pt II −M I (M = Cu, Ag, Au) heterometallic alkynyl complexes in recent years, primarily arising from their intriguing spectroscopic behavior, rich photophysical properties, and diversified structural topology. One of the most intriguing features in these complexes is the tendency to form d 8 −d 10 metal−metal contacts that frequently induce intriguing spectroscopic and optoelectronic properties. It has been demonstrated that participation of the phosphine ligands usually favors formation of ligand-bridged or -unsupported Pt II −M I clusters through d 8 −d 10 metal−metal interactions. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different origins have been proposed for the luminescence observed for complexes 2 a and 2 b , in which diimine ligands complete the M(d 10 ) coordination sphere, depending on the compound type and M(d 10 ). Although the assignments of such emissions are not based on theoretical studies, the proposed origins of the luminescence include neither metal‐centred (MC) transitions nor metal–metal interactions 4a…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we demonstrated that the rare cases of μ-N bridging observed in this series of [Tp*WS 3 Cu 2 ]-supported coordination polymers 2 – 6 is facilitated by the shape and symmetry of the butterfly-shaped cluster core as well as the coordination flexibility of Cu­(I) centers. This assertion is counter-supported by that pyridyls exhibit normal bonding in coordination polymers supported by other types of cluster units. , The C 3 symmetrical Tp* ligands may also contribute to this behavior, reminiscent of the noninnocent nature of Tp and Tp* in the formation of cuboidal [MoS 4 Fe 3 Cl 3 ]-type clusters. It is noteworthy that through the use of monotopic (py), ditopic (bipy and bpea), and tritopic (tpt) ligands, the dimensionality of the resulting coordination polymers goes from 1D ( 2 , 3 ) through 2D ( 4 , 5 ) to 3D ( 6 ).…”
Section: Discussionmentioning
confidence: 99%